A gain-scheduled PID controller for propofol dosing in anesthesia. Issue 20 (2015) - Padula, F.; Ionescu, C.; Latronico, N.; Paltenghi, M.; Visioli, A.; Vivacqua, G.
Abstract: A gain-scheduled proportional-integral-derivative controller is proposed for the closed-loop dosing of propofol in anesthesia (with the bispectral index as a controlled variable). In particular, it is shown that a different tuning of the parameters should be used during the infusion and maintenance phases. Further, the role of the noise filter is investigated.